Facile fabrication of a free-standing superhydrophobic and superoleophilic carbon nanofiber-polymer block that effectively absorbs oils and chemical pollutants from water. (March 2018) - Abdulhussein, Ali T.; Kannarpady, Ganesh K.; Ghosh, Anindya; Barnes, Bailey; Steiner, Richard C.; Mulon, Pierre Yves; Anderson, David E.; Biris, Alexandru S.
Abstract: Due to increased production, transportation, and use of oils and toxic organic solvents, the possibility of spills that cause serious environmental threats and pollution has grown. As a result, effective removal of oils and organic pollutants from water at low cost has become a global challenge. Here, we report the simple, cost-effective fabrication of a free-standing carbon nanofiber-polydimethylsiloxane (CNF/PDMS) nanocomposite block via a solution process using one-step vacuum filtration. The block showed excellent superhydrophobicity and superoleophilicity (water contact angle = 163° and oil contact angle = ∼0°), high mechanical stability, good absorbance capacity, and recyclability. It also exhibited rapid, selective absorption of several types of oils and organic liquids floating on the water surface, as well as heavy oils sunken in water. These findings suggest that the CNF/PDMS block is a promising material for practical applications of oil spills clean up. Graphical abstract: Highlights: A robust, superhydrophobic block was fabricated from inexpensive row materials by a simple one-step method. The block shows rapid, selective absorption of different types of oils and organic solutions. The block is a promising oil sorbent for cleaning up oil and chemical spills from water.